The Extracellular Matrix in the Evolution of Cortical Development and Folding - Amin, Salma; Borrell, Víctor (Frontiers in Cell and Developmental Biology, 2020)
The evolution of the mammalian cerebral cortex leading to humans involved a remarkable sophistication of developmental mechanisms. Specific adaptations of progenitor cell proliferation and neuronal migration mechanisms have been proposed to play major roles in this evolution of neocortical development. One of the central elements influencing neocortex development is the extracellular matrix (ECM). The ECM serves both as structural frame during tissue formation and to present signaling molecules to cells, which directly influences cell behavior and movement. Here we review recent advances in the understanding of the role of ECM molecules on progenitor cell proliferation and neuronal migration, and how these contribute to cerebral cortex expansion and folding. We discuss how transcriptomic studies in human, ferret and mouse identify components of ECM as being candidate key players in cortex expansion during development and evolution. Then we focus on recent functional studies showing that ECM components regulate cortical progenitor cell proliferation, neuron migration and the mechanical properties of the developing cortex. Finally, we discuss how these features differ between lissencephalic and gyrencephalic species, and how the molecular evolution of ECM components and their expression profiles may have been fundamental in the emergence and evolution of cortex folding across mammalian phylogeny.